First discovery of Quercus feeding Nepticulidae (Lepidoptera) in Central America - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Schuster, Jack (Zootaxa, 2013)
Despite the high taxonomic diversity of oaks in Mexico and Central America, no Quercus feeding Nepticulidae have ever been recorded from the region. Here, we present seven species whose larvae are leaf-miners of Quercus (section Lobatae) in Guatemala. Except Stigmella nigriverticella (Chambers 1875), which was previously known from the United States, all other discovered species are new. We describe and name five new species (Stigmella jaguari Remeikis & Stonis, sp. nov., S. lauta Diškus & Stonis, sp. nov., S. sublauta Remeikis & Stonis, sp. nov., S. aurifasciata Diškus & Stonis, sp. nov. and S. guatemalensis Diškus & Stonis, sp. nov.); the remaining new species is described but left unnamed because of lack of adults (i. e. moths and genitalia are described from developed pupae). All seven treated species are illustrated with photographs of the leaf-mines, adults, and genitalia.